Theoretical modelling, design and testing of a novel low pressure spray sprinkler for travelling agricultural irrigation systems. - Budler, Michael John Ian (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.